PELATIHAN MANAJEMEN BAGI PENGELOLA BADAN USAHA MILIK DESA (BUMDES) DAN IBU-IBU PKK DI KECAMATAN TEGALWERU DAU KABUPATEN MALANG - Mohammad Maskan; Bambang Soepeno; Tundung S Patma; Yulis N A (Jurnal Pengabdian kepada Masyarakat, 2020)
The goal of the local government is to provide some assistance to the villagers to stimulatethe community to actively participate in local potential-based development. Therefore, BUMDes inan effort to strengthen the village economy based on the needs and potential of villages(agriculture), in order to increase the income and welfare of the villagers. The establishment ofvillage-owned enterprises has several legal foundations that are the basis and reference in all itsactivities. The establishment of village-owned enterprises (BUMDes) is based on Law No. 32 of2004 on Local Government and Government Regulation No. 72 of 2005 on Village Article 78.BUMDeS managers hold the key to success in its operationalization, therefore management trainingfor BUMDeS managers supported by the PKK is urgently needed to improve the welfare of thevillagers. This needs to be mastered by the managers of BUMDeS and PKK in order to manage theirorganizations through good planning, organizing, direction and supervision so that theorganization's objectives can be achieved effectively and efficiently.